Thermodynamic simulation of a pyro metallurgical process of oxidation of copper sulphide minerals - Nuñez Jara, Pablo (1998)
Thermodynamic simulation models have been developed to observe the behavior of the minor elements Zn, Pb, As, Sb and Bi; as well as the major elements Cu, Fe, Si, 0 and S in the conversion and fusion processes: NORANDA and ISASMELT for the production of copper-rich mattes. The Noranda process shows a steady state model for obtaining a high-grade matte in metallic copper. The lsasmelt process is based on the concept of the two independent reaction sites in the bath (slag-killing interface): rapid oxidation and slow reduction. The heat balance of the process and the distribution thermodynamics of the minor elements are united and expressed in terms of the process variables such as temperature, enriched 02, composition of the charge, degree of matte and content of the magnetite in the Slag and other variables are incorporated into the modeling, which can predict the operating effects of chemical parameters and can also contribute to providing metallurgical control.